Analysis of Selected Public Service Innovation 2022: Variety and Issues - Nurul Hasanah; Reza Fathurrahman (Pelopor Publikasi Akademika, 2023)
To satisfy society’s demands for effective and efficient public services, the Indonesian government through the Ministry of Administrative and Bureaucratic Reform encourages the development of innovation in the public sector by organizing Public Service Innovation Competition (KIPP, Kompetisi Inovasi Pelayanan Publik). In 2022, 3.487 innovations were registered to participate in the competition and 99 of the best innovations were selected from various public agencies. The content analysis results show that the types of innovation that won KIPP were dominated by process innovation. Meanwhile the goal of innovation is mostly to increase people’s satisfaction. Most of the innovations cannot be assessed for their outcome because the results of innovation remain at the output level. Half of the KIPP winning innovations have implemented innovation networks by collaboration with other stakeholders, while only 31.31% of innovations have been replicated. Public service innovation is still focused on process innovation and product innovation. In fact, public issues are not only on how individual people may receive services swiftly as possible but also how to empower people to solve more complex social issues. Governments often experience limited resources to address these problems. For this reason, collaboration is needed with non-government actors such as academics, society and the private sector in a network that is able to create innovative solutions. In addition, the government needs to increase the dissemination of worthy replicable innovations by innovation organizers in other regions. With efforts through the establishment of innovation networks and accelerated replication, public service innovations will not only reach short-term impact outcomes but long-term impact, sustainable and effective outcomes in solving public issues.